An indirect in-cylinder pressure measurement technique based on the estimation of the mechanical strength acting on an engine head screw: development and assessment. (August 2018) - Fiorini, Niccolò; Romani, Luca; Bellissima, Alessandro; Vichi, Giovanni; Bianchini, Alessandro; Ferrara, Giovanni
Abstract: The increasing application of new concepts for the combustion process in internal combustion engines, e.g. HCCI or RCCI, is mainly aimed at reducing pollutant emissions and fuel consumption. A typical drawback of these technologies is the difficulty of properly controlling the combustion process in the area of medium-high brake mean effective pressure (BMEP), where the thermodynamic conditions inside the cylinder promote a very fast combustion process. To this end, the availability of a fast real-time monitoring of the in-cylinder pressure is then becoming pivotal. This is commonly done by means of piezoelectric dynamic pressure sensors, which are indeed very accurate, but also extremely expensive and characterized by a limited durability due to the harsh working conditions. Moving from this background, the present study describes a new methodology to evaluate the in-cylinder pressure by correlating it with the mechanical stress measured by a strain washer installed on an engine head screw. The strain washer can indeed work in a much more favorable environment with respect to a dynamic pressure sensor flush-mounted on the cylinder head (with aggressive hot gasses and high pressure) with direct benefits for its durability and ease of installation. To assess the model capabilities, experimental tests have been carried out on a single-cylinder, 4-stroke engine and on a 2-stroke engine at the laboratory of internal combustion engines of the Università degli Studi di Firenze. The results reported in the study show the direct comparison of the in-cylinder pressure, as a function of the crankshaft angular position, measured directly with a dynamic pressure sensor and indirectly by means of the strain washer. Sound agreement was found between the two, proving the effectiveness of the proposed methodology.